Oral Cadmium in Mice Carrying 5 Versus 2 Copies of the Slc39a8 Gene: Comparison of Uptake, Distribution, Metal Content, and Toxicity. (January 2014) - Schneider, Scott N.; Liu, Zhiwei; Wang, Bin; Miller, Marian L.; Afton, Scott E.; Soleimani, Manoocher; Nebert, Daniel W.
The highly conserved human and mouse SLC39A8 gene encodes the divalent cation/bicarbonate symporter ZIP8 expressed ubiquitously in most cell types. Our bacterial artificial chromosome-transgenic BTZIP8-3 line has 3 additional copies of the Slc39a8 gene in addition to its constitutive diploid pair found in wild-type (WT) mice. In liver, kidney, lung, testis, gastrointestinal tract, and brain, BTZIP8-3 mice are known to express ∼2.5 times greater amounts of ZIP8, compared with WT mice. Herein we administered cadmium chloride (CdCl2 ) in drinking water (100 mg/L through week 2, 200 mg/L through week 4, 400 mg/L through week 8, 800 mg/L through week 12, and 1600 mg/L through week 20, when the experiment was concluded). We postulated that Cd uptake and distribution––and, therefore, toxicity in certain tissues––would be enhanced in BTZIP8-3, compared with WT mice. BTZIP8-3 and WT groups ingested comparable amounts of Cd. Compared with WT, BTZIP8-3 mice showed tissue specific: increases in Cd, zinc, and manganese content and decreases in calcium content. Both Cd-exposed BTZIP8-3 and WT were similar in lower urinary pH; increased plasma alanine and aspartate aminotransferase activities; elevated iron and copper content in liver, kidney, lung, and testis; and higher blood urea nitrogen and kidney weight. Histological changes in liver, kidney, lung, and testis were minimal. In summary, at the daily oral Cd exposures chosen for this study, 5 versus 2 Slc39a8 gene copies result in no differences in Cd toxicity but do cause differences in tissue-specific content of Cd, zinc, manganese, calcium, iron, and copper.